2019
DOI: 10.1111/jpi.12620
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin activates cell death programs for the suppression of uterine leiomyoma cell proliferation

Abstract: The circadian nature of melatonin has a protective effect on the progression of female reproductive cancers, including breast and ovarian cancers. However, the effect of melatonin on the growth of uterine leiomyoma is still unclear. In this study, we found that the growth of uterine leiomyoma ELT3 cells was reduced by treatment with melatonin. Treatment with melatonin increased the distribution of sub-G1 phase and increased DNA condensation in ELT3 cells. Melatonin-induced apoptosis and autophagy cell death pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 55 publications
(56 reference statements)
0
17
0
1
Order By: Relevance
“… 24 Activation cell death programs could suppress cell proliferation of tumor cells. 25 , 26 In addition, there are no research of CYFIP2 in other oncology fields. Our analysis of publicly available databases demonstrated that CYFIP2 expression was decreased in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Activation cell death programs could suppress cell proliferation of tumor cells. 25 , 26 In addition, there are no research of CYFIP2 in other oncology fields. Our analysis of publicly available databases demonstrated that CYFIP2 expression was decreased in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, upregulation of p21, p27, and PTEN protein is another way of melatonin to promote cell programmed death in uterine leiomyoma growth. It also reduced tumor growth in both xenograft and orthotopic uterine tumor mice models [ 89 ]…”
Section: Melatonin and Cancer Hallmarksmentioning
confidence: 99%
“…Melatonin ( N ‐acetyl‐5‐methoxytryptamine) is a type of pineal indolamine and naturally occurring derivative of the amino acid tryptophan with diverse biological activities, which is commonly observed in the nature and occurs in unicellular organisms, fungi, plants and animals. 9 , 10 , 11 Melatonin is initially extracted and identified in the bovine pineal tissues. And now, a vast number of studies indicate that this indolamine could be synthesized in the brain, retina, gastrointestinal tract, thymus and skin, and is mainly produced by the pineal gland at night.…”
Section: Introductionmentioning
confidence: 99%